Method for preparing aluminum nitride ceramic material through injection molding
Through injection molding method and multi-stage process processing, high-precision and complex shape aluminum nitride ceramic products are prepared, solving the problems of high cost, low accuracy and insufficient thermal conductivity in traditional methods, and achieving efficient and precise preparation of aluminum nitride ceramic materials.
Patent Information
- Application Number
- CN202411969643.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The traditional aluminum nitride ceramic molding method has high cost and low accuracy, and the thermal conductivity of aluminum nitride ceramic materials prepared by conventional powder molding is difficult to meet actual needs.
The injection molding method is used to prepare aluminum nitride ceramic materials. By mixing high-purity alumina powder and yttrium oxide powder, multi-stage intensive refining and multi-stage injection and pressure-keeping, combined with solvent degreasing and thermal degreasing processes, high-precision and complex shape aluminum nitride ceramic products are prepared.
The preparation of aluminum nitride ceramic products with high dimensional accuracy and complex shapes is achieved, reducing costs and production cycles, and improving the thermal conductivity and mechanical properties of the material.
Abstract
Description
Technical Field
[0001] The invention relates to the field of aluminum nitride ceramics, and in particular to a method for preparing aluminum nitride ceramic materials by injection molding. Background Art
[0002] Aluminum nitride ceramics are considered to be the first choice for the new generation of high-performance ceramic substrates and packages because of their high thermal conductivity (theoretical thermal conductivity is 320W / (m·K)), low dielectric constant and dielectric loss, non-toxicity, insulation, good mechanical properties, and thermal expansion coefficients that match those of chip materials such as silicon and gallium arsenide. In recent years, with the rapid development of microelectronics technology, the demand for high-dimensional precision special-shaped packaging and heat dissipation devices for large-scale integrated circuits, high-power microwave devices, and semiconductor equipment is doubling every year, thus requiring more and more miniature, complex-shaped, high-thermal conductivity aluminum nitride ceramic parts. However, aluminum nitride ceramics are hard and brittle, and it is difficult to prepare parts with the required shape and dimensional accuracy using traditional processing methods.
[0003] The traditional forming methods of aluminum nitride ceramics include dry pressing, isostatic pressing, tape casting, etc. The green bodies formed by dry pressing and isostatic pressing require a lot of mechanical processing to form complex structures. The aluminum nitride ceramic parts prepared by these two methods are costly, and the shape and dimensional accuracy are difficult to meet the requirements. Tape casting is mainly used to form aluminum nitride ceramic substrates; powder injection molding is a new near-net-shape forming technology formed by introducing modern plastic injection molding technology into the field of powder metallurgy. The biggest feature of this technology is that it can directly prepare parts with complex shapes, and because it is a fluid filling mold, there is basically no mold wall friction, the density of the formed green body is uniform, and the dimensional accuracy is high. However, as the injection molding method of aluminum nitride ceramics disclosed in Chinese patent CN117430426A, the thermal conductivity of the aluminum nitride ceramic material formed by it is difficult to meet the needs of actual production in some cases. Summary of the invention
[0004] In order to solve the technical problems raised in the above background technology that the cost and precision of parts in dry pressing and isostatic pressing are low and the electrical conductivity of aluminum nitride ceramic materials prepared by conventional powder molding is difficult to meet the requirements, the present invention provides a method for preparing aluminum nitride ceramic materials by injection molding, which can not only prepare miniature aluminum nitride ceramic products with high dimensional accuracy and complex shapes by net size molding, but also has the advantages of high mechanization and automation, high production efficiency, short molding cycle, etc., and can carry out customized production of multiple varieties in batches.
[0005] The specific technical solution of the present invention is: a method for preparing aluminum nitride ceramic material by injection molding, comprising the following steps: 1) Mixing and stirring 92 to 100 parts by weight of high-purity alumina powder and 0 to 8 parts by weight of yttrium oxide powder to obtain a mixed powder; 2) 40-45 parts of mixed powder and 10-20 parts of binder are mixed by weight, heated, stirred evenly, and then 40-50 parts of mixed powder are added, four stages of internal mixing are successively performed, and then the mixed materials are extruded and pelletized to obtain injection feed; 3) The injection feed is subjected to two-stage injection and two-stage pressure holding to obtain an injection green embryo; 4) After solvent degreasing and thermal degreasing of the injection green body, sintering is performed to obtain aluminum nitride ceramic material. The method for preparing aluminum nitride ceramic material by injection molding provided by the present invention has a liquid die, and parts with complex shapes can be directly prepared with basically no mold wall friction, and aluminum nitride ceramic material with higher dimensional accuracy can be prepared. At the same time, yttrium oxide is used as a sintering aid, which not only helps to reduce the sintering temperature, but also improves the thermal conductivity of the aluminum nitride ceramic material; multi-stage process is used for feeding, and injection feeding with better fluidity can be obtained, thereby improving the accuracy of making aluminum nitride ceramic workpieces; multi-stage injection and multi-stage pressure holding are used during injection molding, which can effectively avoid the appearance of flash and fly holes in the injection process, and ensure the density, strength and dimensional accuracy of the green embryo.
[0006] Further, in step 2), the specific operation of the four-stage banburying is as follows: in the first stage, stirring at a temperature of 170-200° C. and a rotation speed of 10-40 r / min for 30-60 min; in the second stage, stirring at a temperature of 130-160° C. and a rotation speed of 10-40 r / min for 20-50 min; in the third stage, stirring at a temperature of 170-200° C. and a rotation speed of 10-40 r / min for 20-50 min; in the fourth stage, stirring at a temperature of 130-160° C. and a rotation speed of 10-40 r / min for 20-50 min.
[0007] Furthermore, in step 3), the feeding temperature of the injection feeding is 150-180°C.
[0008] Further, in step 3), injection feeding, the first stage of injection, the speed is 110-200 mm / s, the pressure is 100-150 MPa, and the time is 0.1-1 s; the second stage of injection, the speed is 70-110 mm / s, the pressure is 150-250 MPa, and the time is 0.1-1 s; the first stage of pressure holding, the speed is 60-100 mm / s, the pressure is 20-40 MPa, and the pressure holding time is 1-5 s; the second stage of pressure holding, the speed is 30-60 mm / s, the pressure is 40-80 MPa, and the pressure holding time is 1-5 s.
[0009] Furthermore, the components of the binder are 20 to 30 parts of high-density polyethylene, 45 to 55 parts of paraffin wax, 10 to 20 parts of polypropylene, 5 to 8 parts of vinyl bisstearamide and 3 to 5 parts of zinc stearate in parts by weight.
[0010] Furthermore, in step 4), the degreasing solvent is n-heptane, which is more environmentally friendly than trichloroethylene as a degreasing solvent. Secondly, the boiling point of n-heptane is much lower than that of kerosene, which is conducive to recycling after evaporation and cooling.
[0011] Furthermore, in step 4), solvent degreasing is as follows: immersing the injected green embryo in a degreasing solvent and keeping it at 50-60° C. for 20-30 hours, then removing the degreasing solvent and keeping it at 95-105° C. for 5-10 hours.
[0012] Preferably, the degreasing solvent is evaporated, cooled and then recycled.
[0013] Furthermore, in step 4), the thermal degreasing temperature is 500-600° C., and the thermal degreasing time is 3-5 hours.
[0014] Furthermore, in step 4), the sintering temperature is 1750-1850° C., and the sintering time is 6-10 hours.
[0015] Furthermore, the heating rate during thermal debinding is 0.1 to 1°C / min, and the heating rate during sintering is 0.1 to 1°C / min.
[0016] Preferably, pressureless sintering is used for sintering, and the sintering atmosphere is nitrogen.
[0017] Compared with the prior art, the beneficial effects of the present invention are: Aluminum nitride ceramic products prepared by injection molding have high dimensional accuracy, avoiding a large amount of machining of the ceramics in the later stage, saving raw materials, machining costs and time.
[0018] The use of a multi-stage process to refining ceramic powder helps to obtain injection feed with good fluidity so that the powder can fully fill the mold cavity during injection.
[0019] During injection molding, multi-stage injection and multi-stage pressure holding are used to avoid the appearance of flash, air holes, etc. during the injection process, and to ensure the density, strength and dimensional accuracy of the green body.
[0020] 4) Using yttrium oxide as a sintering aid not only helps to reduce the sintering temperature, but also improves the thermal conductivity of aluminum nitride ceramic materials; using n-heptane as a degreasing solvent is more environmentally friendly than trichloroethylene. Secondly, the boiling point of n-heptane is much lower than that of kerosene, which is conducive to evaporative cooling and recycling. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with the embodiments.
[0022] Example 1 1) Preparation of injection feed 3.8 kg of high-purity aluminum nitride powder and 0.2 kg of yttrium oxide powder were placed in a mixer and stirred for 4 hours at a speed of 30 r / min to obtain 4 kg of mixed powder; the binder and 2 kg of mixed powder were added to the mixer and granulated, heated to 195°C, stirred for 50 minutes at a speed of 30 r / min; and the remaining 2 kg of mixed powder was added to the mixer and granulated for four stages of mixing, with the first stage at a temperature of 195°C, stirring for 30 minutes and a speed of 30 r / min, and the second stage at a temperature of 150°C and stirring for 20 minutes. , speed 30r / min, third stage temperature 180℃, stirring 30min, speed 30r / min, fourth stage temperature 140℃, stirring 20min, speed 30r / min; finally, use screw extrusion to mix, screw temperature 125℃, screw speed 35r / min, start the pelletizing system, pelletizing speed 500r / min, and obtain injection feeding, wherein the binder is 150g high-density polyethylene, 300g paraffin, 90g polypropylene, 36g vinyl bisstearamide, and 24g zinc stearate mixed evenly.
[0023] 2) Injection molding The injection feed prepared in step 1) is added to an injection machine for injection molding to obtain an injection green embryo. The internal barrel temperature of the injection machine is 150-180° C., the mold temperature is 50-55° C., the first-stage injection speed is 120 mm / s, the pressure is 125 MPa, and the time is 0.25 s. The second-stage injection speed is 100 mm / s, the pressure is 160 MPa, and the time is 0.23 s. The first-stage holding speed is 70 mm / s, the pressure is 35 MPa, and the holding time is 2 s. The second-stage holding speed is 30 mm / s, the pressure is 50 MPa, and the holding time is 0.5 s.
[0024] 3) Degreasing and sintering The green body obtained in step (3) is placed in a dissolution furnace, heated to 60°C and kept warm for 20 hours at a heating rate of 3°C / min, and the paraffin is removed; then the n-heptane is extracted, the extracted n-heptane is evaporated and cooled, and then recovered and reused, and the temperature of the dissolution furnace is heated to 100°C and kept warm for 8 hours; the obtained solvent-degreased green body is placed in a degreasing furnace, heated to 600°C and kept warm for 5 hours at a heating rate of 1°C / min, and the obtained hot-degreased green body is placed in a vacuum sintering furnace with a sintering temperature of 1800°C and a heating rate of 0.5°C / min. It is kept warm at 1800°C for 8 hours, and naturally cooled to room temperature to obtain aluminum nitride ceramic material. Nitrogen is required to be passed through the whole process to ensure a nitrogen atmosphere in the furnace.
[0025] 4) Performance testing The density, thermal conductivity and flexural strength of the aluminum nitride ceramic material obtained in step 3) are tested. The thermal conductivity test is calculated using the formula of the product of thermal diffusion coefficient, specific heat and density, where the thermal diffusion coefficient is measured using an ultra-high temperature laser thermal conductivity meter, and the specific heat is measured using a differential scanning calorimeter; the density test uses a precision density balance, and the test temperature is 25°C; the flexural strength test uses a universal testing machine, and the test method is a three-point flexural strength test method. Among them, the density of the aluminum nitride ceramic material produced by the scheme in this embodiment is 3.33g / cm 3 , thermal conductivity is 204W / (m·k) and bending strength is 322MPa.
[0026] Comparative Example 1 The difference between this comparative example and Example 1 is that in step 1), one-step refining is performed, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of injection feed 3.8 kg of high-purity aluminum nitride powder and 0.2 kg of yttrium oxide powder are placed in a mixer and stirred for 4 hours at a speed of 30 r / min to obtain 4 kg of mixed powder; the binder and 2 kg of mixed powder are added to the mixer and granulated, the temperature is raised to 195°C, and stirred for 50 minutes at a speed of 30 r / min; then the remaining 2 kg of mixed powder is added to the mixer and granulated and continued to be stirred for 2 hours at a speed of 30 r / min. Finally, the screw is used for extrusion mixing, the screw temperature is 125°C, the screw speed is 35 r / min, the pelletizing system is started, pelletizing is carried out, and the speed is 500 r / min to obtain injection feeding, wherein the binder is 150 g of high-density polyethylene, 300 g of paraffin, 90 g of polypropylene, 36 g of vinyl bisstearamide, and 24 g of zinc stearate, which are evenly mixed.
[0027] 2) Injection molding The injection feed prepared in step 1) is added to an injection machine for injection molding to obtain an injection green embryo. The internal barrel temperature of the injection machine is 150-180° C., the mold temperature is 50-55° C., the first-stage injection speed is 120 mm / s, the pressure is 125 MPa, and the time is 0.25 s. The second-stage injection speed is 100 mm / s, the pressure is 160 MPa, and the time is 0.23 s. The first-stage holding speed is 70 mm / s, the pressure is 35 MPa, and the holding time is 2 s. The second-stage holding speed is 30 mm / s, the pressure is 50 MPa, and the holding time is 0.5 s.
[0028] 3) Degreasing and sintering The green body obtained in step (3) is placed in a dissolution furnace, heated to 60°C and kept warm for 20 hours at a heating rate of 3°C / min, and the paraffin is removed; then the n-heptane is removed, and the temperature of the dissolution furnace is heated to 100°C and kept warm for 8 hours; the solvent-degreased green body obtained is placed in a degreasing furnace, heated to 600°C and kept warm for 5 hours at a heating rate of 1°C / min; the hot-degreased green body obtained is placed in a vacuum sintering furnace, the sintering temperature is 1800°C, the heating rate is 0.5°C / min, and the green body is kept warm at 1800°C for 8 hours, and then naturally cooled to room temperature to obtain aluminum nitride ceramic material. Nitrogen is required to be passed through the entire process to ensure a nitrogen atmosphere in the furnace.
[0029] 4) Performance testing The density, thermal conductivity and flexural strength of the aluminum nitride ceramic material obtained in step 3) were tested. The density of the aluminum nitride ceramic material prepared by the scheme in this comparative example was 3.30 g / cm 3 , thermal conductivity is 193W / (m·k) and bending strength is 304MPa.
[0030] Table 1 Effect of step-by-step calcination on the properties of aluminum nitride ceramic materials secret refining <![CDATA[Density / (g / cm 3 )]]> Thermal conductivity (W / (m·k)) Bending strength(MPa) Example 1 Four sections 3.33 204 322 Comparative Example 1 One section 3.30 193 304 From the data in Table 1, the use of segmented mixing (i.e., multi-stage process) for the feed to prepare aluminum nitride ceramic materials is helpful to obtain injection feed with good fluidity and more uniform density, which can better fill the mold cavity during injection molding, ensure the strength, density uniformity and dimensional accuracy of the green body, and thus obtain aluminum nitride ceramic materials with higher density, thermal conductivity and bending strength.
[0031] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, in step 2), the injection molding has only one injection stage and one pressure holding stage, and the rest of the process is the same as that of Example 1. The specific steps are as follows: 1) Preparation of injection feed 3.8 kg of high-purity aluminum nitride powder and 0.2 kg of yttrium oxide powder were placed in a mixer and stirred for 4 hours at a speed of 30 r / min to obtain 4 kg of mixed powder; the binder and 2 kg of mixed powder were added to the mixer and granulated, heated to 195°C, stirred for 50 minutes at a speed of 30 r / min; and the remaining 2 kg of mixed powder was added to the mixer and granulated for four stages of mixing, with the first stage at a temperature of 195°C, stirring for 30 minutes and a speed of 30 r / min, and the second stage at a temperature of 150°C and stirring for 20 minutes. , speed 30r / min, third stage temperature 180℃, stirring 30min, speed 30r / min, fourth stage temperature 140℃, stirring 20min, speed 30r / min; finally, use screw extrusion to mix, screw temperature 125℃, screw speed 35r / min, start the pelletizing system, pelletizing speed 500r / min, and obtain injection feeding, wherein the binder is 150g high-density polyethylene, 300g paraffin, 90g polypropylene, 36g vinyl bisstearamide, and 24g zinc stearate mixed evenly.
[0032] 2) Injection molding The injection feed prepared in step 1) is added into an injection machine for injection molding to obtain an injection green embryo. The internal barrel temperature of the injection machine is 150-180°C, the mold temperature is 50-55°C, the injection speed is 120 mm / s, the pressure is 125 MPa, and the time is 0.25 s. The holding speed is 70 mm / s, the pressure is 35 MPa, and the holding time is 2 s.
[0033] 3) Degreasing and sintering The green body obtained in step (3) is placed in a dissolution furnace, heated to 60°C and kept warm for 20 hours at a heating rate of 3°C / min, and the paraffin is removed; then the n-heptane is extracted, and the extracted n-heptane is evaporated and cooled for recycling, and the temperature of the dissolution furnace is heated to 100°C and kept warm for 8 hours; the obtained solvent-degreased green body is placed in a degreasing furnace, heated to 600°C and kept warm for 5 hours at a heating rate of 1°C / min, and the obtained hot-degreased green body is placed in a vacuum sintering furnace, the sintering temperature is 1800°C, the heating rate is 0.5°C / min, and it is kept at 1800°C for 8 hours, and then naturally cooled to room temperature to obtain aluminum nitride ceramic material. Nitrogen is required to be passed through the whole process to ensure a nitrogen atmosphere in the furnace.
[0034] 4) Performance testing The density, thermal conductivity and flexural strength of the aluminum nitride ceramic material obtained in step 3) were tested. The density of the aluminum nitride ceramic material prepared by the scheme in this comparative example was 3.28 g / cm 3 , thermal conductivity is 190W / (m·k) and bending strength is 289MPa.
[0035] Table 2 Effect of segmented injection molding on the properties of aluminum nitride ceramic materials Whether to use segmented injection molding <![CDATA[Density / (g / cm 3 )]]> Thermal conductivity (W / (m·k)) Bending strength(MPa) Example 1 yes 3.33 204 322 Comparative Example 2 no 3.28 190 289 From the data in Table 2, injection molding uses multi-stage injection and multi-stage pressure holding to reduce or even avoid the appearance of flash and pores during the injection process, obtain a green body with higher density and strength, and make the density and bending strength of the final aluminum nitride ceramic material meet the required requirements.
[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that in this comparative example, yttrium oxide is not added, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of injection feed 4kg of high-purity aluminum nitride powder was placed in a mixer and stirred for 4 hours at a speed of 30r / min; a binder and 2kg of high-purity aluminum nitride powder were added to the mixer and granulated, heated to 195°C, stirred for 50min, and rotated at 30r / min; then the remaining 2kg of high-purity aluminum nitride powder was added to the mixer and granulated for four stages of mixing, with the first stage at 195°C, stirring for 30min, and a speed of 30r / min; the second stage at 150°C, stirring for 20min, and a speed of 30r / min n, the third stage temperature is 180°C, stirring for 30 minutes, and the speed is 30r / min, the fourth stage temperature is 140°C, stirring for 20 minutes, and the speed is 30r / min; finally, the screw is used for extrusion mixing, the screw temperature is 125°C, the screw speed is 35r / min, the pelletizing system is started, and the pelletizing speed is 500r / min to obtain injection feeding, wherein the binder is 150g high-density polyethylene, 300g paraffin, 90g polypropylene, 36g vinyl bisstearamide, and 24g zinc stearate mixed evenly.
[0037] 2) Injection molding The injection feed prepared in step 1) is added to an injection machine for injection molding to obtain an injection green embryo. The internal barrel temperature of the injection machine is 150-180° C., the mold temperature is 50-55° C., the first-stage injection speed is 120 mm / s, the pressure is 125 MPa, and the time is 0.25 s. The second-stage injection speed is 100 mm / s, the pressure is 160 MPa, and the time is 0.23 s. The first-stage holding speed is 70 mm / s, the pressure is 35 MPa, and the holding time is 2 s. The second-stage holding speed is 30 mm / s, the pressure is 50 MPa, and the holding time is 0.5 s.
[0038] 3) Degreasing and sintering The green body obtained in step (3) is placed in a dissolution furnace, heated to 60°C and kept warm for 20 hours at a heating rate of 3°C / min, and the paraffin is removed; then the n-heptane is removed, and the temperature of the dissolution furnace is heated to 100°C and kept warm for 8 hours; the solvent-degreased green body obtained is placed in a degreasing furnace, heated to 600°C and kept warm for 5 hours at a heating rate of 1°C / min; the hot-degreased green body obtained is placed in a vacuum sintering furnace, the sintering temperature is 1800°C, the heating rate is 0.5°C / min, and the green body is kept warm at 1800°C for 8 hours, and then naturally cooled to room temperature to obtain aluminum nitride ceramic material. Nitrogen is required to be passed through the entire process to ensure a nitrogen atmosphere in the furnace.
[0039] 4) Performance testing The density, thermal conductivity and flexural strength of the aluminum nitride ceramic material obtained in step 3) were tested. The density of the aluminum nitride ceramic material prepared by the scheme in this embodiment was 3.24 g / cm 3 , thermal conductivity is 81W / (m·k) and bending strength is 308MPa.
[0040] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, 0.3 kg of yttrium oxide is added in step 1), and the rest of the process is the same as that in Example 1, and the specific steps are as follows: 1) Preparation of injection feed 3.7 kg of high-purity aluminum nitride powder and 0.3 kg of yttrium oxide powder were placed in a mixer and stirred for 4 hours at a speed of 30 r / min to obtain 4 kg of mixed powder; the binder and 2 kg of mixed powder were added to the mixer and granulated, heated to 195°C, stirred for 50 minutes at a speed of 30 r / min; and the remaining 2 kg of mixed powder was added to the mixer and granulated for four stages of mixing, with the first stage at a temperature of 195°C, stirring for 30 minutes and a speed of 30 r / min, and the second stage at a temperature of 150°C and stirring for 20 minutes. , speed 30r / min, third stage temperature 180℃, stirring 30min, speed 30r / min, fourth stage temperature 140℃, stirring 20min, speed 30r / min; finally, use screw extrusion to mix, screw temperature 125℃, screw speed 35r / min, start the pelletizing system, pelletizing speed 500r / min, and obtain injection feeding, wherein the binder is 150g high-density polyethylene, 300g paraffin, 90g polypropylene, 36g vinyl bisstearamide, and 24g zinc stearate mixed evenly.
[0041] 2) Injection molding The injection feed prepared in step 1) is added to an injection machine for injection molding to obtain an injection green embryo. The internal barrel temperature of the injection machine is 150-180° C., the mold temperature is 50-55° C., the first-stage injection speed is 120 mm / s, the pressure is 125 MPa, and the time is 0.25 s. The second-stage injection speed is 100 mm / s, the pressure is 160 MPa, and the time is 0.23 s. The first-stage holding speed is 70 mm / s, the pressure is 35 MPa, and the holding time is 2 s. The second-stage holding speed is 30 mm / s, the pressure is 50 MPa, and the holding time is 0.5 s.
[0042] 3) Degreasing and sintering The green body obtained in step (3) is placed in a dissolution furnace, heated to 60°C and kept warm for 20 hours at a heating rate of 3°C / min, and the paraffin is removed; then the n-heptane is removed, and the temperature of the dissolution furnace is heated to 100°C and kept warm for 8 hours; the solvent-degreased green body obtained is placed in a degreasing furnace, heated to 600°C and kept warm for 5 hours at a heating rate of 1°C / min; the hot-degreased green body obtained is placed in a vacuum sintering furnace, the sintering temperature is 1800°C, the heating rate is 0.5°C / min, and the green body is kept warm at 1800°C for 8 hours, and then naturally cooled to room temperature to obtain aluminum nitride ceramic material. Nitrogen is required to be passed through the entire process to ensure a nitrogen atmosphere in the furnace.
[0043] 4) Performance testing The density, thermal conductivity and flexural strength of the aluminum nitride ceramic material obtained in step 3) were tested. The density of the aluminum nitride ceramic material prepared by the scheme in this embodiment was 3.34 g / cm 3 , thermal conductivity is 184W / (m·k) and bending strength is 320MPa.
[0044] Table 3 Effect of sintering aid yttrium oxide on the properties of aluminum nitride ceramic materials <![CDATA[AlN:Y2O3 (mass ratio)]]> <![CDATA[Density / (g / cm 3 )]]> Thermal conductivity (W / (m·k)) Bending strength(MPa) Example 1 95:5 3.33 204 322 Comparative Example 3 100:0 3.24 81 308 Comparative Example 4 92.5:7.5 3.34 184 320 From the data in Table 3, when yttrium oxide is not added in the preparation process or the addition amount of yttrium oxide is excessive, the thermal conductivity of the final aluminum nitride ceramic material will decrease. The reason is analyzed as follows: aluminum nitride with yttrium oxide added will form yttrium aluminate liquid phase during sintering, which reduces the sintering temperature, densifies the aluminum nitride ceramic and eliminates O defects, so the density and thermal conductivity are relatively high; but when yttrium oxide is added excessively, the density will increase, and the yttrium aluminate phase will be too much (the thermal conductivity of the yttrium aluminate phase is lower than that of aluminum nitride), which will lead to a decrease in the thermal conductivity of the aluminum nitride ceramic material.
[0045] Example 2 1) Preparation of injection feed 3.8 kg of high-purity aluminum nitride powder and 0.2 kg of yttrium oxide powder were placed in a mixer and stirred for 4 hours at a speed of 30 r / min to obtain 4 kg of mixed powder; the binder and 2 kg of mixed powder were added to the mixer and granulated, heated to 195°C, stirred for 50 minutes at a speed of 30 r / min; and the remaining 2 kg of mixed powder was added to the mixer and granulated for four stages of mixing, with the first stage at a temperature of 180°C, stirring for 40 minutes and a speed of 20 r / min, and the second stage at a temperature of 140°C and stirring for 30 minutes. , speed 20r / min, third stage temperature 170℃, stirring 40min, speed 20r / min, fourth stage temperature 130℃, stirring 30min, speed 30r / min; finally, use screw extrusion mixing, screw temperature 125℃, screw speed 35r / min, start the pelletizing system, pelletizing speed 500r / min, and obtain injection feeding, wherein the binder is 120g high-density polyethylene, 330g paraffin, 90g polypropylene, 42g vinyl bisstearamide, and 18g zinc stearate mixed evenly.
[0046] 2) Injection molding The injection feed prepared in step 1) is added to an injection machine for injection molding to obtain an injection green embryo. The internal barrel temperature of the injection machine is 150°C, the mold temperature is 55°C, the first-stage injection speed is 110 mm / s, the pressure is 130 MPa, and the time is 0.10 s, the second-stage injection speed is 90 mm / s, the pressure is 200 MPa, and the time is 0.52 s, the first-stage holding speed is 70 mm / s, the pressure is 30 MPa, and the holding time is 3 s, and the second-stage holding speed is 40 mm / s, the pressure is 60 MPa, and the holding time is 3 s.
[0047] 3) Degreasing and sintering The green body obtained in step (3) is placed in a dissolution furnace, heated to 50°C and kept warm for 30 hours at a heating rate of 3°C / min, and the paraffin is removed; then the n-heptane is extracted, the extracted n-heptane is evaporated and cooled, and then recovered and reused, and the temperature of the dissolution furnace is heated to 90°C and kept warm for 9 hours; the obtained solvent-degreased green body is placed in a degreasing furnace, heated to 500°C and kept warm for 8 hours at a heating rate of 1°C / min; the obtained hot-degreased green body is placed in a vacuum sintering furnace, the sintering temperature is 1800°C, the heating rate is 0.5°C / min, and it is kept warm at 1800°C for 8 hours, and then naturally cooled to room temperature to obtain aluminum nitride ceramic material. Nitrogen is required to be passed through the whole process to ensure a nitrogen atmosphere in the furnace.
[0048] 4) Performance testing The density, thermal conductivity and flexural strength of the aluminum nitride ceramic material obtained in step 3) are tested. The thermal conductivity test is calculated using the formula of the product of thermal diffusion coefficient, specific heat and density, wherein the thermal diffusion coefficient is measured using an ultra-high temperature laser thermal conductivity meter, and the specific heat is measured using a differential scanning calorimeter; the density test uses a precision density balance, and the test temperature is 25°C; the flexural strength test uses a universal testing machine, and the test method is a three-point flexural strength test method.
[0049] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0050] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing aluminum nitride ceramic material by injection molding, characterized in that: The following steps are involved: 1) Mixing and stirring 92-100 parts by weight of high-purity alumina powder and 0-8 parts by weight of yttrium oxide powder to obtain a mixed powder; 2) Mix 40-45 parts of mixed powder and 10-20 parts of binder by weight, heat up, stir evenly, then add 40-50 parts of mixed powder, perform four-stage internal mixing, extrude the mixed materials, cut into pellets to obtain injection feed; 3) The injection feed is subjected to two-stage injection and two-stage pressure holding to obtain an injection green embryo; 4) The injection green body is subjected to solvent degreasing and thermal degreasing, and then sintered to obtain aluminum nitride ceramic material.
2. The method for preparing aluminum nitride ceramic material by injection molding according to claim 1, characterized in that: In step 2), the specific operation of the four-stage refining is: In the first stage, stirring is performed at a temperature of 170-200°C and a rotation speed of 10-40 r / min for 30-60 min; The second stage is stirring at a temperature of 130-160°C and a rotation speed of 10-40 r / min for 20-50 min; The third stage is stirring at a temperature of 170-200°C and a rotation speed of 10-40 r / min for 20-50 min; In the fourth stage, stirring is carried out for 20 to 50 minutes at a temperature of 130 to 160°C and a rotation speed of 10 to 40 r / min.
3. The method for preparing aluminum nitride ceramic material by injection molding according to claim 1, characterized in that: In step 3), the feeding temperature of the injection feeding is 150~180℃.
4. A method for preparing aluminum nitride ceramic material by injection molding according to claim 1 or 3, characterized in that: In step 3), injection feeding, In the first stage of injection, the speed is 110~200mm / s, the pressure is 100~150MPa, and the time is 0.1~1s; The second stage of injection, the speed is 70~110mm / s, the pressure is 150~250MPa, and the time is 0.1~1s; The first stage of pressure holding is at a speed of 60-100 mm / s, a pressure of 20-40 MPa, and a holding time of 1-5 s. The second stage of pressure holding has a speed of 30~60mm / s, a pressure of 40~80MPa, and a pressure holding time of 1~5s.
5. The method for preparing aluminum nitride ceramic material by injection molding according to claim 1, characterized in that: The components of the binder are 20-30 parts of high-density polyethylene, 45-55 parts of paraffin wax, 10-20 parts of polypropylene, 5-8 parts of vinyl bisstearamide and 3-5 parts of zinc stearate in parts by weight.
6. The method for preparing aluminum nitride ceramic material by injection molding according to claim 1, characterized in that: In step 4), the degreasing solvent is n-heptane.
7. A method for preparing aluminum nitride ceramic material by injection molding according to claim 1 or 6, characterized in that: In step 4), solvent degreasing is as follows: immersing the injected embryo in a degreasing solvent and keeping it at 50-60°C for 20-30 hours, then removing the degreasing solvent and keeping it at 95-105°C for 5-10 hours.
8. The method for preparing aluminum nitride ceramic material by injection molding according to claim 1, characterized in that: In step 4), the thermal debinding temperature is 500-600°C, and the thermal debinding time is 3-5 hours.
9. The method for preparing aluminum nitride ceramic material by injection molding according to claim 1, characterized in that: In step 4), the sintering temperature is 1750-1850°C and the sintering time is 6-10 hours.
10. The method for preparing aluminum nitride ceramic material by injection molding according to claim 8 or 9, characterized in that: The heating rate during thermal debinding is 0.1~1℃ / min, and the heating rate during sintering is 0.1~1℃ / min.
Citation Information
Patent Citations
Injection molding method of aluminum nitride ceramic
CN117430426A
Aluminium nitride ceramic wafer and preparation method thereof
CN102344281A
Aluminum nitride ceramic injection molding method
CN107915490A
Dielectric waveguide ceramic filter and preparation method thereof
CN111342177A
Shell and preparation method thereof
CN115488995A